SOME NEW FIFTH MULTIPLICATIVE ZAGREB INDICES OF PAMAM DENDRIMERS - Kulli, V.R. (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper, we introduce the general fifth multiplicative M-Zagreb indices, fifth multiplicative product connectivity index, fifth multiplicative sum connectivity index of a molecular graph and determine these multiplicative indices for PAMAM dendrimers. Also we compute the fourth multiplicative atom bond connectivity index and fifth multiplicative geometric-arithmetic index for PAMAM dendrimers. Â  Keywords: molecular graph, fifth multiplicative indices, PAMAM dendrimer. Mathematics Subject Classification: 05C05, 05C07, 05C35.